The Influence of Leadership Style, Work Motivation, and Organizational Culture on Employee Performance at RSU PKU Muhammadiyah Purbalingga - Awaludin; Sri Wahyuni; Herni Justiana Astuti; Ani Kusbandiyah (Management Analysis Journal, 2024)
This study examined the effect of leadership style, work motivation, and organizational culture on employee performance through work discipline as an intervening variable at RSU PKU Muhammadiyah Purbalingga. The research design was quantitative research, and the data collection method used was a questionnaire. The research population was 223 RSU PKU Muhammadiyah Purbalingga employees, and the sample used was 100 respondents. Sampling uses a sampling technique with the purposive sampling method. The data analysis method used the PLS (Partial least square) with a structural equation model (SEM) path analysis approach using the Smart PLS application program. The results of this study indicated that Leadership style and organizational culture influence the performance of RSU PKU Muhammadiyah Purbalingga employees. Work motivation and work discipline do not affect the performance of RSU PKU Muhammadiyah Purbalingga employees. Leadership style and work motivation also influence work discipline, while organizational culture does not influence the work discipline of employees at RSU PKU Muhammadiyah Purbalingga. Leadership style, work motivation and work discipline do not influence the performance of RSU PKU Muhammadiyah Purbalingga employees through work discipline